A mathematics education research Aaenda in Latin America motivated by Coronavirus Pandemic (2020)
RESUMEN: The pandemic and its disruption of social dynamics, including school dynamics, necessitates a review of both the proposals for education in situations of confinement and the research that must be carried out to account for exceptional educational situations. It is likely that this pandemic is only the first circumstance that has highlighted the need to investigate more decisively areas that have not been previously considered or have been put aside. This document presents the case of three Latin American countries, Mexico, Colombia, and Chile, in relation to educational difficulties generated by the pandemic, with respect to regional actions on the educational problems that have been revealed, and proposes regional research agendas for the Mathematics Education research community.